Upaya meningkatkan Kemampuan Guru dalam Proses Kegiatan Belajar Mengajar di SMAN 3 Batam Melalui Supervisi Akademik Tahun Pelajaran 2017/2018 - Vivi Kusuma Effendi (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
The purpose of this study was (1) Knowing the implementation of academic supervision to improve the ability of teachers in teaching and learning activities in SMA Negeri 3 Batam. (2) Analyzing an increase in the ability of teachers in the process of teaching and learning activities through the implementation of academic supervision in SMA Negeri 3 Batam. This research is a classroom action research. The research design uses the Kemmis & Tagart stages which consist of 4 stages (1) planning, (2) implementation, (3) Observation, and (4) Reflection. The subjects in this study were students of class X in the academic year 2017/2018. The number of students as the study population was 350 students consisting of 35 students each from class X. Data collection techniques using test techniques and observation sheets. Data analysis techniques used descriptive analysis. The results of the study concluded that (1) Principal's academic supervision was carried out effectively to improve the ability of teachers, especially professional competence in the teaching and learning process in schools. (2) Teachers' academic supervision is basically to make some improvements, including students having critical thoughts, so that they can discuss with fellow teachers and students more deeply and can prove teacher performance, and the achievement of learning objectives in the curriculum. The principle of academic supervision is carried out regularly, on the basis of mutual consultation to build professional teacher coordination and creativity. School principals are advised to further improve supervision such as monitoring and guiding teachers, supervising intensity in schools and guidance in meeting the goals of National Education in order to improve learning in the classroom as a form of maximum service to students at school.